Educators' Role In Risk Management At Sps Al-Qur'an Al- Muhajirin - Dewi Rosita; Lisa Listiqomah; Nita Prasetia; Nurhabibah Nurhabibah; Nurlia Nurlia (JURNAL ECONOMINA, 2026)
This study examines the roles of educators and education personnel in implementing risk management at SPS Al-Qur'an Al-Muhajirin Balikpapan, an Islamic-based early childhood education institution. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving one school principal, five teachers, and three parents. While prior research has largely treated school management and risk management as separate domains, this study integrates human resource roles with risk management within an Islamic early childhood education setting. Findings show that educators play a key role in identifying potential risks, safeguarding student safety, and undertaking preventive measures against risks encountered both within and outside the school environment, while the school principal manages risk-related administration, maintains facilities and infrastructure, and ensures the safety and comfort of the school community. Risk management is implemented through student supervision, safety procedures, parental communication, and a disciplinary culture grounded in Islamic values. The study contributes theoretically by strengthening the concept of risk management within Islamic education and offers practical implications regarding the importance of collaboration among school stakeholders in fostering a safe, comfortable, and inclusive learning environment.